2015
DOI: 10.3109/07420528.2015.1065269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time-of-day on neuromuscular function in untrained men: Specific responses of high morning performers and high evening performers

Abstract: , K. (2015). Effects of time-of-day on neuromuscular function in untrained men: Specific responses of high morning performers and high evening performers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Assuming a standard sleep-wake cycle, muscle strength is lowest in the morning (~0600) and greatest in the afternoon and early evening (1600 -1800). This has been observed with isometric strength of the elbow flexors (142)(143)(144) and ankle plantarflexors (69), isometric and isokinetic strength of the knee extensors (11,23,67,116,147,160,196,230,292,293,363,377,441), isoinertial strength of the lower limbs (77), tests of hand and finger strength (116,152,172,264,270,377), and the isometric midthigh pull (83,396). The increase in strength in the afternoon and early evening is usually 4 -10%, and it coincides with an increase in core body temperature (11,67,116,143,147,160,363,396).…”
Section: Administrative Strategies and The Test Environmentmentioning
confidence: 78%
“…Assuming a standard sleep-wake cycle, muscle strength is lowest in the morning (~0600) and greatest in the afternoon and early evening (1600 -1800). This has been observed with isometric strength of the elbow flexors (142)(143)(144) and ankle plantarflexors (69), isometric and isokinetic strength of the knee extensors (11,23,67,116,147,160,196,230,292,293,363,377,441), isoinertial strength of the lower limbs (77), tests of hand and finger strength (116,152,172,264,270,377), and the isometric midthigh pull (83,396). The increase in strength in the afternoon and early evening is usually 4 -10%, and it coincides with an increase in core body temperature (11,67,116,143,147,160,363,396).…”
Section: Administrative Strategies and The Test Environmentmentioning
confidence: 78%
“…Thus, our findings have implications for athletic communities in terms of practice/workout schedules to enhance athletic potential—in particular, a ‘one time fits all’ schedule might not optimize performance for all athletes. Coaches and trainers may want to adopt diverse or flexible schedules, and it should be noted that the optimal scheduling times might differ for strength versus speed versus endurance training [21622]. …”
Section: Discussionmentioning
confidence: 99%
“…Maximal neuromuscular performance has been shown to fluctuate with time-of-day, with 5-15 % higher strength values observed in the evening [8,13,24,36,46] compared to the morning. However, in the case of endurance performance, the effect of diurnal rhythms seems to dissipate [11,15,17], although some studies have demonstrated that tolerance of high-intensity endurance exercise (e. g., performed as cycling) is higher in the evening [2,6].…”
Section: Introductionmentioning
confidence: 99%